Effect of Deformation Parameters on Thermomechanical Behaviour of GH500 Superalloy - Fu Hao, Wang Minshi, Dai Pengchao (Teshugang)
Different parameters such as deformation temperature and deformation rate were set for thermal compression tests， using the Thermecmastor-Z thermal simulation testing machine. The stress-strain curves and metallographic structures were analyzed to systematically study the high-temperature thermal deformation behavior and morphological evolution of the GH500 superalloy. The results showed that the stress-strain curves exhibited characteristics of work hardening， dynamic recovery， and dynamic recrystallization， with stress significantly increasing as the deformation temperature decreased and the deformation rate increased. At a deformation rate of 1 s-1， as the deformation temperature increased， the microstructure of the alloy evolved from deformed grains and small clusters of grains into fully recrystallized grains. When the deformation temperature was ≥1 130 ℃， the volume fraction and size of the dynamic recrystallized grains of the alloy significantly increased with the rise in deformation rate. At a deformation temperature of 1 180 ℃ and a deformation rate of 1 s-1， the alloy underwent complete dynamic recrystallization with no deformed grains， resulting in fine and uniform grains. Based on the stress-strain curves and microstructural evolution obtained from hot compression tests， suitable forging processes have been explored. The heating temperature was set between 1 130 ℃ and 1 150 ℃， and the reduction speed was 10 mm/s to 15 mm/s with the deformation rate betweem 0.04s-1  and 0.06 s-1 during the forging process. The produced disc alloy exhibit a basically uniform grain structure. After standard heat treatment， the room temperature tensile strength， hardness， and high-temperature durability of disc alloy meet the standard requirements.